2020
DOI: 10.1088/1748-9326/ab90a6
|View full text |Cite
|
Sign up to set email alerts
|

Denitrification hotspots in intertidal mixing zones linked to geologic heterogeneity

Abstract: The mixing between fresh and saline groundwater in beach aquifers promotes biogeochemical transformations that affect nutrient fluxes to the coastal ocean. We performed variable-density groundwater flow and reactive transport simulations with geostatistical representations of sedimentary structure to understand the influence of heterogeneity on groundwater dynamics and denitrification in intertidal mixing zones. Ensemble-averaged simulation results show that heterogeneity can enhance mixing between fresh and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 56 publications
1
28
0
Order By: Relevance
“…Indeed, Tamborski et al (2017b) observed significant radon, radium, and dissolved Mn 2+ enrichments at this depth horizon. Geologic heterogeneity can act to both modify groundwater flow paths and enhance biogeochemical transformations within the STE (Heiss et al, 2020). However, denitrification cannot explain the differences in δ 15 N-NO 3 − and δ 18 O-NO 3 − compositions (Figures 3A, 4).…”
Section: Subsurface Processes and Variabilitymentioning
confidence: 99%
“…Indeed, Tamborski et al (2017b) observed significant radon, radium, and dissolved Mn 2+ enrichments at this depth horizon. Geologic heterogeneity can act to both modify groundwater flow paths and enhance biogeochemical transformations within the STE (Heiss et al, 2020). However, denitrification cannot explain the differences in δ 15 N-NO 3 − and δ 18 O-NO 3 − compositions (Figures 3A, 4).…”
Section: Subsurface Processes and Variabilitymentioning
confidence: 99%
“…Reactive transport simulations in homogeneous intertidal aquifers show that denitrification rates are highest within the freshwater-saltwater mixing zone (Heiss et al, 2017). However, observations of reaction rates in intertidal aquifers show spatial heterogeneity (Kim et al, 2017(Kim et al, , 2019, and simulations indicate that nitrate removal rate through denitrification may be 80% greater in heterogeneous aquifers compared to their homogeneous equivalents (Heiss et al, 2020). Thus, it is critical to understand both mixing in intertidal aquifers and the effects of heterogeneity in aquifer sediments.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical simulations of water flow toward the root layer were conducted with randomized heterogeneous fields; a simple linear correlation was assumed between height of the capillary fringe and saturated K. Their results revealed that an increase in heterogeneity at the root-soil interface leads to high root water uptake rates. While a number of previous studies have explored the effects of geologic heterogeneity on flow and transport processes in coastal aquifer systems, the studies only considered spatial variability in K (Geng et al, 2020b;Heiss, Michael, & Koneshloo, 2020;Lu et al, 2013;Michael et al, 2016;Pool et al, 2015;Sebben et al, 2015). In coastal aquifers, due to oceanic forcing (e.g., tides and waves), variably saturated conditions are ubiquitously observed in nearshore beach systems; therefore, it is important to consider heterogeneity of sediment capillarity when investigating coastal flow and transport processes.…”
Section: Introductionmentioning
confidence: 99%